Детский фразеологический словарь в картинках: справ. изд. / [С.В. Волков] - Волков Сергей Владимирович (АСТ [и др.], 2010)
Экземпляры: Ч/з ДБ, ф. 2, 4 (20111102) / Инвентарный номер: 97628 / Цена: 173.52 / Сис.шифр: 81.2Рус-4 / Авт.знак: В 67 / ББК: 81.2Рус-4